Making the European polity : reflexive integration in the EU - Eriksen, Erik Oddvar, 1955- (Routledge studies on democratizing Europe ;, 2005)
The European Union now consists of twenty-five member states, but there is confusion and disagreement about its future design. This book investigates how the Union should develop and organise itself.